Beyond Competency: Developing Critical Digital Capabilities in Nursing Students Through Freirean Pedagogy - Wynn, Matthew Oliver (Nursing inquiry, 2025)
ABSTRACT The digitalisation of healthcare is transforming nursing practice, presenting unique opportunities and challenges that demand more than technical competence from nursing professionals. Despite the growing integration of digital tools, nursing remains in the ‘foothills of digital transformation’, with significant gaps in the critical and theoretical frameworks required to navigate this shift effectively. This article explores how Paulo Freire's critical pedagogy may address these gaps by fostering critical digital skills in nursing students. Drawing on Freire's concepts of problem‐posing education, conscientization, dialogue and praxis, the article proposes a pedagogical model that encourages students to critically examine the socio‐political and ethical implications of digital tools within their practice. By aligning Freirean principles with contemporary nursing challenges, the article argues for a shift away from solely competency‐based frameworks toward educational approaches that promote reflective, dialogical, and ethically informed engagement with technology. The limitations of Freirean pedagogy, including its difficulty in evidencing direct outcomes, are discussed alongside its potential to cultivate a philosophically engaged nursing workforce capable of navigating the complexities of a digital healthcare environment and its associated impact on the profession. This approach underscores the importance of preserving nursing's core ethical and relational values while embracing the transformative potential of digital technologies.